Beyond the Last Glacial Maximum: Island endemism is best explained by long‐lasting archipelago configurations. Issue 2 (21st November 2018) - Norder, Sietze J.; Proios, Konstantinos; Whittaker, Robert J.; Alonso, María R.; Borges, Paulo A. V.; Borregaard, Michael K.; Cowie, Robert H.; Florens, F. B. Vincent; de Frias Martins, António M.; Ibáñez, Miguel; Kissling, W. Daniel; de Nascimento, Lea; et al.
Abstract: Aim: To quantify the influence of past archipelago configuration on present‐day insular biodiversity patterns, and to compare the role of long‐lasting archipelago configurations over the Pleistocene to configurations of short duration such as at the Last Glacial Maximum (LGM) and the present‐day. Location: 53 volcanic oceanic islands from 12 archipelagos worldwide—Azores, Canary Islands, Cook Islands, Galápagos, Gulf of Guinea, Hawaii, Madeira, Mascarenes, Pitcairn, Revillagigedo, Samoan Islands and Tristan da Cunha. Time period: The last 800 kyr, representing the nine most recent glacial–interglacial cycles. Major taxa studied: Land snails and angiosperms. Methods: Species richness data for land snails and angiosperms were compiled from existing literature and species checklists. We reconstructed archipelago configurations at the following sea levels: the present‐day high interglacial sea level, the intermediate sea levels that are representative of the Pleistocene and the low sea levels of the LGM. We fitted two alternative linear mixed models for each archipelago configuration using the number of single‐island endemic, multiple‐island endemic and (non‐endemic) native species as a response. Model performance was assessed based on the goodness‐of‐fit of the full model, the variance explained by archipelago configuration and model parsimony. Results: Single‐island endemic richness in both taxonomic groups was best explained by intermediate palaeo‐configuration (positively by area change, and negatively by palaeo‐connectedness), whereas non‐endemic native species richness was poorly explained by palaeo‐configuration. Single‐island endemic richness was better explained by intermediate archipelago configurations than by the archipelago configurations of the LGM or present‐day. Main conclusions: Archipelago configurations at intermediate sea levels—which are representative of the Pleistocene—have left a stronger imprint on single‐island endemic richness patterns on volcanic oceanic islands than extreme archipelago configurations that persisted for only a few thousand years (such as the LGM). In understanding ecological and evolutionary dynamics of insular biota it is essential to consider longer‐lasting environmental conditions, rather than extreme situations alone.